Konflik Peran Ganda dengan Stres Kerja pada Polisi Wanita di Polres Ogan Ilir - Desi Purnamasari; Kiki Cahaya Setiawan (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study alms to determine the relationship between work family conflict and work stress on police women of Polres OI. This research is a correlation quantitative study. The subjects is 31 police woman. There are hypotheses in this research, there is relationship between work family conflict and work stress of the police woman of the Polres OI. The measuring instrument in this study uses two scales, namely the scale of work family conflict and the scale work stress. Data analysis used pearson product moment analysis by SPSS v.25 for windows. The results of this research, there is no relationship between work family conflict and work stress the factory police woman which the significance value is 0,809 (p>0,05).